2011
DOI: 10.1111/j.1600-0404.2011.1605.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in Parkinson’s disease unaffected by deep brain stimulation

Abstract: STN-DBS offered no considerable impact on autonomic cardiovascular control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Overall, these studies found reduced HRV-using both time-domain and frequencydomain measures-in PD patients compared to controls. [18][19][20][21] The evidence that cardiac dysautonomia is present before the motor onset of PD is more limited. The Cardiovascular Health Study, a community-based cohort of men and women age 65 years and older, measured HRV in 24-hour Holter records from 1,587 individuals free of PD, 44 of whom developed PD during 14 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies found reduced HRV-using both time-domain and frequencydomain measures-in PD patients compared to controls. [18][19][20][21] The evidence that cardiac dysautonomia is present before the motor onset of PD is more limited. The Cardiovascular Health Study, a community-based cohort of men and women age 65 years and older, measured HRV in 24-hour Holter records from 1,587 individuals free of PD, 44 of whom developed PD during 14 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings describe autonomic responses, during only a limited period of time, with large individual variability, promoting a limited view of the autonomic mechanisms in control of cardiac activity [9,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ANS in Parkinson's patients include perturbations in cardiovascular regulation, hypotension, especially in orthostatic position, and sexual dysfunction [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supported by a more recent controlled study that reported improved orthostatic hypotension in PD patients after DBS. 76 Another controlled study including 28 PD patients proposed that the vagal component of the arterial-cardiac baroreflex improved postoperatively. 77 Dafsari et al .…”
Section: Dbs Effect On the Autonomic Domainmentioning
confidence: 99%